2015
DOI: 10.1039/c5fo00548e
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract improves the oxidative state of the liver and brain in rats with adjuvant-induced arthritis

Abstract: The purpose of the study was to evaluate the possible effects of the administration of a green tea extract on the oxidative state of the liver and brain of adjuvant-induced arthritic rats, a model for human rheumatoid arthritis. Daily doses of 250 mg kg(-1) (59.8 mg catechins per kg) for 23 days were administered. This treatment produced significant diminutions in protein and lipid damage in liver, brain and plasma. It also diminished the tissue ROS contents and increased the antioxidant capacity of the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Unsurprisingly, the results obtained in the present study with Ilex paraguariensis are very similar to the results obtained in a previous study of our group with Camellia sinensis (green tea). 43 The green tea extract improved the oxidative state of the adjuvant-induced arthritic rats by affecting practically the same parameters in the liver, brain and plasma as the yerba mate extract: diminution of ROS contents, diminution of damage to proteins and lipids and increases in the antioxidant defenses. 43 There are also studies indicating antiinflammatory actions for green tea and green tea components.…”
Section: Food and Function Papermentioning
confidence: 98%
See 1 more Smart Citation
“…Unsurprisingly, the results obtained in the present study with Ilex paraguariensis are very similar to the results obtained in a previous study of our group with Camellia sinensis (green tea). 43 The green tea extract improved the oxidative state of the adjuvant-induced arthritic rats by affecting practically the same parameters in the liver, brain and plasma as the yerba mate extract: diminution of ROS contents, diminution of damage to proteins and lipids and increases in the antioxidant defenses. 43 There are also studies indicating antiinflammatory actions for green tea and green tea components.…”
Section: Food and Function Papermentioning
confidence: 98%
“…43 The green tea extract improved the oxidative state of the adjuvant-induced arthritic rats by affecting practically the same parameters in the liver, brain and plasma as the yerba mate extract: diminution of ROS contents, diminution of damage to proteins and lipids and increases in the antioxidant defenses. 43 There are also studies indicating antiinflammatory actions for green tea and green tea components. 44,45 These and other similarities certainly reinforce the parallelism of both species as medicinal plants worldwide.…”
Section: Food and Function Papermentioning
confidence: 98%
“…Several studies have shown that the reactive oxygen species (ROS) participate in the generation of RA [59, 60]. High level of ROS in the liver of adjuvant-induced arthritis in rats seems to be resulting from both a deficient antioxidant defense and a stimulated prooxidant system [61, 62]. It has been reported that the livers of collagen induced arthritis rats exhibited a higher oxygen consumption, and the efficiency of mitochondrial energy transduction did not decrease [63].…”
Section: The Influence Of Liver In Abnormal Glucose Metabolism In Ramentioning
confidence: 99%
“…RA is not a disease typically involving the CNS, but brain dysfunctions occur in 20 to 30% of rheumatic patients (Appenzeller et al 2004). There are only few studies describing oxidative stress and brain damage during experimental arthritis such as AA (Skurlova et al 2010;Skurlova et al 2011;de Almeida Gonçalves et al 2015). Carnosine is accumulated in excitable tissues (brain, heart and skeletal muscles) of vertebrates in large amounts (Abe 1995).…”
Section: Discussionmentioning
confidence: 99%